The Control of Anthrax Disease: Diagnosis, Vaccination and Investigation - Rahmat Setya Adji; Lily Natalia (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2006)
Anthrax is a bacterial disease caused by Bacillus anthracis attacking both animal and human (zoonosis) . The disease is normally associated with domestic livestock such as sheep, goats, and cattle, but humans are also infected due to exposure or comsuming infected animals . The control of anthrax in humans and animals involves developing a diagnostic method for B. anthracis detection and confirmation of anthrax, prevention by vaccines, and disease investigation . Rapid and more accurate diagnosis techniques for anthrax should be developed for improving the conventional method used in Indonesia . Vaccines are effective against anthrax . Current anthrax vaccine used in Indonesia is spores vaccine produced from a non-encapsulated, toxigenic. Sterne strain 34F2 of B. anthracis . The use of this vaccine occasionally causes local pain, necroses at the inoculation site, subcutaneous oedema and occasionally death of the animal . Several vaccines have been developed recently such as sub unit vaccine, anthrax vaccine absorbed (AVA), that contains a protective antigen (PA) component of the anthrax toxin as the major protective immunogen and is usually used in humans. In endemic areas of anthrax, outbreaks still routinely occur almost yearly . Monitoring of the epidemiological patterns of the disease has to be carried out by field investigation . Key words: Anthrax, Bacillus anthracis, zoonotic disease, disease control